Investigation of the viscosifying and stabilizing effect of hydrophilic and hydrophobic clays in emulsified oil-based fluids (Research, Society and Development, 2021)
Bentonites are extensively investigated for acting as viscosifying and stabilizing agents for emulsified fluids. The properties of drilling fluids are extremely important for the success of oil well drilling. However, the purification of clays is necessary to promote an improvement in the rheological behavior of the dispersions. Like natural bentonite clays, organophilic clays obtained from sodium bentonite clays are of enormous industrial importance due to their high degree of swelling in water, and quarternary ammonium salts. In this study, the influence of the clay type is investigated rheologically in emulsified fluids of different mass proportions oil/water (O/W): 50/50, 70/30, 80/20, 90/10 and 95/05 under the concentration 6000ppm. The clay samples were characterized by FRX, DRX AND TG/DTA. All oil-based emulsified fluids were analyzed through macroscopic and rheological morphological observations. Purified sludge green (hydrophilic) and organophilic sludge green (hydrophobic) clays were tested as viscosifying and stabilizing agents for emulsions. From the results, it was possible to verify the chemical composition of the clays, with the organophilic clay being the one with the greatest loss to fire, the efficiency of the surfactant intercalation in the slime-green organophilic clay shown in the X-ray diffractograms, as well as the events of mass loss, where the organophilic slime-green showed a greater loss. Rheologically, the results confirmed that only the emulsion containing sludge-green clay of mass fraction 50/50 (O/W) was physically stable.